Influence of film and modified atmosphere on sensory quality of roasted apple cv. Reineta - Marcelo, V.; Valenciano, J. B.; Guerra, M.; Boto, J. A. (Spanish Journal of Agricultural Research, 2010)
The aim of this study was to determine the influence of film type and modified atmosphere on the sensory quality of roasted apple cv. Reineta. Roasted apples were packaged using two different films, LORE 90 COOK and CN 300, under two different modified atmosphere conditions, Extendapak 1 ® (100% N2) and Extendapak 47 ® (7.0% CO2 2.5% O2 90.5% N2). The Packaged apples were stored for 210 days at 3ºC. Sensory analyses were performed every 14 days until the end of the storage period. Each sample was made up of 178 fruit for each type of packaging and for each storage time. No significant differences were found between the newly elaborated and the stored roasted apples according to the difference test until the 84th day of storage. No significant differences were found in the visual attributes of the apples, except for colour, neither between types of packaging nor between storage times. Significant differences were found in olfactory-gustatory attributes, odour intensity, sweet taste and alcoholic taste between type of packaging whereas significant differences were found between storage times for all olfactory-gustatory attributes. Juiciness was the only textural attribute that was significantly different between type of packaging and between storage times. When the film was less permeable of the film, the better the original properties of roasted apple cv. Reineta were kept better. There were significant differences between modified atmospheres, so Extendapak 1 ® was more appropriate than Extendapak 47 ® to keep the original characteristics of roasted apple cv. Reineta for a longer time.